THE INFLUENCE OF ONLINE CUSTOMER REVIEW AND ONLINE CUSTOMER RATING ON GOFOOD PURCHASE DECISIONS IN THE GOJEK APPLICATION - Lila Febriana Kausaha; Ida Hidayanti; Ririn Damayanti (IAIN Surakarta, 2023)
This study aims to determine the effect of the dependent and independent variables partially and simultaneously. The research methodology used a quantitative method by collecting data through distributing questionnaires, the population in this study were users of the Gojek application in Ternate City, the sampling technique used purposive sampling and snowball sampling with 125 respondents. Data were obtained by using multiple linear regression analysis with the SPSS 25 program. The results indicate that partially online customer reviews have a significant effect on purchasing decisions for GoFood on the Gojek application, while online customer ratings partially have no significant effect on purchasing decisions for GoFood on the Gojek application, and simultaneously or together online customer reviews and online customer ratings have an effect significantly to GoFood purchasing decisions on the Gojek application.